Pengaruh Perspektif Mengenai Penerapan Ice Breaking dan Pemberian Reward Terhadap Hasil Belajar Siswa SMA Pada Mata Pelajaran Ekonomi: The Influence of the Application of Ice Breaking and Rewards on High School Students Learning Outcomes in Economics - Sari, Agi Permata; Hermawan, Yoni; Kurniawan, Kurniawan (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This research was motivated by low student learning outcomes, which were attributed to a monotonous classroom atmosphere and unengaging teaching methods. The purpose of this study was to determine the influence of implementing ice breaking and giving rewards on student learning outcomes in the Economics subject at SMA Negeri 9 Tasikmalaya. This study employed a quantitative method with a descriptive survey approach. The instrument used was a questionnaire with a Likert scale. The sample for this study consisted of students from grades X and XI of the Social Sciences department. The data analysis results indicate that both ice breaking and reward giving have a significant effect on student learning outcomes, both partially and simultaneously. Simultaneously, the contribution of these two variables to learning outcomes reached 52.4%. This finding confirms that a teacher's creativity in applying enjoyable learning strategies, such as ice breaking and rewards, can enhance both student motivation and learning outcomes.